VENOUS ULCERS IN PATIENTS TREATED AT FAMILY HEALTH UNITS IN NATAL, BRAZIL: PREVALENCE AND SOCIODEMOGRAPHIC AND HEALTH CHARACTERIZATION (Fiep Bulletin - online, 2014)
This is a descriptive study aimed at identifying the prevalence of venous ulcers (VU), and the sociodemographic and health characteristics of VU patients treated in the Family Health Units (FHUs). The target population was composed of 74 VU patients treated by Family Health Program (FHP) teams in the 31 FHUs. The study was approved by the Ethics Committee of the Universidade Federal do Rio Grande do Norte (protocol no. 55/05). Data collection, using a structured interview, was performed in the patients' residence and in the FHUs. The data were organized in an Excel column chart and transferred to SPSS software, version 14.0 for descriptive analysis using 2x2 contingency tables and inferential statistics (Chi-square-÷2, Pearson's correlation and p-value
Keywords: Venus ulcers; Family Health Program; prevalence; characterization